2019
DOI: 10.1016/j.fertnstert.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of progestogen supplementation for luteal phase support in fresh in vitro fertilization cycles

Abstract: Objective: To evaluate the effectiveness of progestogen supplementation in improving clinical pregnancy rates in women undergoing fresh IVF cycles and to compare different routes, start times, durations and estrogen co-administration regimen.Design: Comprehensive systematic review and meta-analysis. Setting: University. Patients: Women undergoing fresh IVF cycles who did and did not receive progestogen supplementation. Intervention(s): Summary odds ratios (ORs) were calculated by binomial logistic regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…A “uterine first-pass effect” that occurs when steroid hormones are delivered through the vagina has been suggested [ 27 ]. Vaginal administration of progesterone supplements in the luteal phase has been proven to have uterine effects that exceed the response that can be expected from the circulating levels of progesterone [ 28 , 29 ], with ~10-fold progesterone delivery to the uterus in ~7-fold lower circulating concentrations than intramuscular injections [ 30 , 31 ]. In our previous pilot study, we demonstrated that intermittent vaginal injection of rhFSH in women receiving IVF treatment resulted in proper folliculogenesis, fertilization rate, implantation rate, and pregnancy rates [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A “uterine first-pass effect” that occurs when steroid hormones are delivered through the vagina has been suggested [ 27 ]. Vaginal administration of progesterone supplements in the luteal phase has been proven to have uterine effects that exceed the response that can be expected from the circulating levels of progesterone [ 28 , 29 ], with ~10-fold progesterone delivery to the uterus in ~7-fold lower circulating concentrations than intramuscular injections [ 30 , 31 ]. In our previous pilot study, we demonstrated that intermittent vaginal injection of rhFSH in women receiving IVF treatment resulted in proper folliculogenesis, fertilization rate, implantation rate, and pregnancy rates [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic review suggested that the day after oocyte pick up is the best time for initiation of LPS and that continuing more than three wk does not improve clinical pregnancy rates (85). The ESHRE guidelines recommended that LPS should be started in the interval time between the evening of the day of ovum pick up and day 3 post oocyte retrieval (39).…”
Section: The Ideal Time For Initiating Lpsmentioning
confidence: 99%
“…В пользу микронизированного прогестерона говорит еще один систематический обзор и метаанализ, включающий 82 статьи (26 726 пациенток) [25]. Установлено, что на благоприятный исход беременности повлияло назначение прогестерона с первого дня после получения ооцитов в программах ВРТ.…”
Section: Obstetrics and Gynecologyunclassified